2023
DOI: 10.1101/2023.03.28.534550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel loss of type VI secretion systems in two multi-drug resistantEscherichia colilineages

Abstract: The repeated emergence of pandemic multi-drug resistant (MDR) Escherichia coli clones is a threat to public health globally. In recent work, drug resistant E. coli were shown to be capable of displacing commensal E. coli in the human gut. We hypothesise that there are three factors potentially responsible for the apparent competitive advantage of drug resistant E. coli clones: enhanced metabolic capabilities; production of lytic phage or bacteriocins; or the presence of a type VI secretion system (T6SS). We em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…Both F084 and F016 strains out-competed the commensal 822-E8 strain achieving 96.1% and 80.7% of the total It is possible that F084 and MDR F016 are out-competing the commensal 822-E8 strain due to phage or production of a secreted toxin. Previous data from our group has shown that an ST131 strain retards growth of both ST73 and ST10 strains in LB broth [16]. Therefore, we grew each strain in LB broth overnight, filter sterilised the spent medium before mixing in a 1:1 ratio with fresh LB, and investigated the growth kinetics of all strains in the presence of supernatant from a competing strain.…”
Section: Non-mdr Expec and Mdr Expec Are Efficient Colonisers Of Germ...mentioning
confidence: 99%
“…Both F084 and F016 strains out-competed the commensal 822-E8 strain achieving 96.1% and 80.7% of the total It is possible that F084 and MDR F016 are out-competing the commensal 822-E8 strain due to phage or production of a secreted toxin. Previous data from our group has shown that an ST131 strain retards growth of both ST73 and ST10 strains in LB broth [16]. Therefore, we grew each strain in LB broth overnight, filter sterilised the spent medium before mixing in a 1:1 ratio with fresh LB, and investigated the growth kinetics of all strains in the presence of supernatant from a competing strain.…”
Section: Non-mdr Expec and Mdr Expec Are Efficient Colonisers Of Germ...mentioning
confidence: 99%